Pemikiran Neo-modernisme dalam Hubungan Agama dan Negara di Indonesia: Studi Komparatif Pemikiran Nurcholish Madjid Dan Abdurrahman Wahid - Fitri, Donna Ramadhan; Afifi, Abdullah A; Abbas, Afifi Fauzi (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2022)
Neo-modernism emerged when the term post-modernism began when the term began to become a common discourse when many experts began to get displeased with the negative effects that modernity, either from the aspect of sociocultural structure or scientific aspects. Neo-modernism, if traced to its existence, is in the thoughts of Fazlur Rahman (1970). While in Indonesia itself has Neo-modernism figures namely Nurcholish Madjid and Abdurrahman Wahid. As moralists and democrats, they have a complete, comprehensive, inclusive, and even free understanding of Islam. Therefore, their ideological and political actions often cause controversy. Even if they differ in practice, they have a paradigm of Islamic thought. Since Cak Nur put forward the jargon "Islam yes" and "Partai Islam no" in the 1970s, the integration of Islam and national opinion began to surface. Since then, the struggle for Islam through cultural channels has continued, and Muslims have also begun to participate in nation-building. In 1984, when NU under the leadership of Gus Dur approved Pancasila as the only precept, the relationship between Islam and the State grew stronger.